Exploring the Strengths and Weaknesses of Islamic Banking in Türkiye: A Multi-Generational Perspective - Yenice, Ali Can; Orhan, Zeyneb Hafsa; Orhan, Zeyneb Hafsa (My University, 2025)
Purpose – This study aims to perform a SWOT analysis of Islamic banking (IB) in Türkiye, incorporating perspectives from Islamic bankers across different generations. The research seeks to identify the current strengths, weaknesses, opportunities and threats shaping the future of IB in Türkiye, which boasts a history spanning nearly 40 years. Design/methodology/approach – This study uses a qualitative research method with a case study design. Participants’ views were gathered through semi-structured questions to conduct a multi- generational SWOT analysis of IB in Türkiye. A purposive sampling technique was used to identify research participants. Online interviews, lasting between 60 and 120min, were conducted with bank employees across nearly all levels, including Chief Executive Officers, General Managers/Chief Operating Officers, Chief Financial Officers, department managers, branch managers and employees, directors and analysts. Findings – In the study, 19 themes and 26 subthemes were identified based on the participants’ SWOT analyses. The key strengths of IB in Türkiye include a large Muslim population, strong religious sensitivity, ongoing transformation with governmental support and extensive branch–small- and medium-sized enterprises experience. However, its weaknesses involve regulatory challenges, governance issues, problems related to public Islamic banks, employee transfers, a lack of product diversity and inclusiveness, as well as low levels of Islamic financial literacy. On the other hand, opportunities arise from the rapid growth of the capital market, the emergence of digital banking, Türkiye’s strategic geographic location and its strong growth trajectory. Meanwhile, threats include employee migration from conventional banks, an increasing focus on performance metrics, nomenclature challenges and the accelerating pace of digitalization. Originality/value – To the best of the authors’ knowledge, this study is the first in the literature to conduct a SWOT analysis encompassing all generations of Islamic bankers in Türkiye. The participants, ranging from senior executives to entry-level employees, have raised numerous issues being discussed for the first time in the literature, offering groundbreaking insights into ongoing debates.
Keywords: Islamic finance; Islamic banking; Participation banking; Türkiye; SWOT analysis